Kajian Perilaku Konsumen terhadap Strategi Pemasaran Teh Herbal di Kota Bogor - E. Srivishnu Herlambang; Musa Hubeis; Nurheni Sri Palupi (MANAJEMEN IKM: Jurnal Manajemen Pengembangan Industri Kecil Menengah, 2011)
The purpose of this study is to know the general behavior of the consumers of herbal tea in Bogor; In particular aims to: (1) Identify the internal factors that include a consumer culture and the psychological factors that influence the purchase decision process product herbal tea products by consumers, (2) Identify and analyze factors in the process of product purchase decisions by consumers herbal tea, (3) Identify the behavior of consumer product marketing strategy of herbal tea. This study was conducted at the outlets own by PT. Liza Herbal International (LHI), in the city of Bogor. The population in this study is everyone in Bogor that consume their herbal tea product. Sampling is done by accidental sampling method, namely the consumers of herbal tea that is found across the research area (outlets that sell products herbal tea production by Liza Herbal). From 23 outlets located in the city of Bogor, each outlet is taken five respondents; a total of 115 respondents. This study used descriptive methods and analytical analysis, especially principle component analysis. Based on the analysis of three major components obtained the most influence the purchase decision process of herbal tea are variable price, brand and variable of the womb. The mixture marketing strategy needed that can be done are (1) Maintain and improve the quality of herbal tea (2) The discounted price for a certain number of purchases, (3) Promotion and products through the exhibition website and (4) Service is ready and to ensure continuity between the availability of herbal tea. Development of product strategy marketing herbal tea that can be done with the company's strategy is Strengths, Weaknesses, Opportunities and Threats (SWOT) analysis as follows: SO strategy are (a) increase the productivity of marketing network and (b) improvement of service, strategy ST are (a) improve and maintain the quality of the resulting product, (b) increase cooperation and mutually beneficial partnership with the farmers plant and herbal industry similar, WO strategy are (a) the production costs by increasing efficiency, especially in the procurement of raw materials, (b) Diversification of products, and strategies WT are (a) increase production technology and quality with the standard of quality desired by the market, (b) improve the distribution channel.